2015, market conditions for independent productions to be seen in the Mexican film industry - Barradas, Andrés (2016)
This research shows some points of view to understand the distribution and exhibition issues in Mexican film industry. There are some official data published by the Instituto Mexicano de Cinematografía (Imcine), the Cámara Nacional de la Industria Cinematográfica (Canacine) as well as expert opinions inside and outside the film industry. The main issue is focused on independent films made in Mexico (with less than 10 copies) and the way these are being distributed and exhibited in Mexico in a market usually dominated by foreign companies and national oligopolies.